2009
DOI: 10.1093/schbul/sbp024
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Dysfunction in Unaffected First-Degree Relatives of Patients Suffering From Schizophrenia

Abstract: Recent studies revealed cardiac autonomic dysfunction in patients with acute schizophrenia, which appears to be mainly related to reduced vagal and increased sympathetic modulation. To understand the significance of cardiac autonomic function in patients with schizophrenia, we extended these studies to relatives of patients. In this study, we assessed cardiac autonomic modulation in healthy first-degree relatives of patients with schizophrenia (n = 36) to investigate a putative genetic influence. Data were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 54 publications
5
46
2
Order By: Relevance
“…This algorithm is widely used and implemented in many file compressors, such as Winzip. Its application in RR time series has been described elsewhere (28,29). The ratio of the compressed to the original time series length represents an index of entropy and is referred to as compression entropy Hc.…”
Section: Nonlinear Compression Entropymentioning
confidence: 99%
See 1 more Smart Citation
“…This algorithm is widely used and implemented in many file compressors, such as Winzip. Its application in RR time series has been described elsewhere (28,29). The ratio of the compressed to the original time series length represents an index of entropy and is referred to as compression entropy Hc.…”
Section: Nonlinear Compression Entropymentioning
confidence: 99%
“…A detailed description has been published previously (13,29). Spontaneous sequences of at least three consecutive beats were analyzed, when an increased systolic blood pressure (SBP) of at least 1 mm Hg caused an increased BBI of at least 5 ms (bradycardic sequence) or a decreased SBP caused a decreased beat-tobeat interval (tachycardic sequence).…”
Section: Baroreflex Sensitivity (Brs)mentioning
confidence: 99%
“…The present study indicates that people with low resting HRV show heightened activities in similar brain areas for neutral face stimuli. There is extensive evidence suggesting that reduced HRV was associated with serious psychiatric illness, such as bipolar disorder and schizophrenia (Bär et al, 2009;Castro et al, 2008). Severity of psychotic symptoms of schizophrenia was associated with cardiac autonomic disturbance (Bär et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these factors, the dysregulation of the autonomic nervous system (ANS) during acute psychosis has become evident for patients with schizophrenia in studies carrying out heart rate variability (HRV) analysis. Studies applying HRV analyses found reduced vagal and increased sympathetic modulation, indicating a cardiac autonomic dysregulation in patients with schizophrenia and partly in their healthy first-degree relatives [6][7][8][9][10][11][12][13]. The pattern of autonomic dysfunction seen in patients and their relatives might indicate underlying diseaseinherent genetic vulnerability, especially as it was shown by Busjahn et al [14] that a genetic dependency of autonomic parameters (HRV) exists.…”
Section: Introductionmentioning
confidence: 99%